2011
DOI: 10.1016/j.jmii.2011.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological analysis of adult perianal abscess

Abstract: Escherichia coli was the predominant pathogen isolated from perianal abscesses in patients without DM. Klebsiella pneumoniae, however, was the predominant pathogen isolated in DM patients. In both DM and non-DM patients, more than 90% of K pneumoniae isolates showed in vitro sensitivity to first-generation cephalosporins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 20 publications
2
25
0
1
Order By: Relevance
“…Literature has shown that about 40% patients develop a fistula in ano after primary incision and drainage of perianal abscess (15)(18). As perianal abscess frequently co-exists with fistula in ano, failure to identify and treat the internal opening at the time of primary operation may result in chronic fistulation 1 …”
mentioning
confidence: 99%
“…Literature has shown that about 40% patients develop a fistula in ano after primary incision and drainage of perianal abscess (15)(18). As perianal abscess frequently co-exists with fistula in ano, failure to identify and treat the internal opening at the time of primary operation may result in chronic fistulation 1 …”
mentioning
confidence: 99%
“…Infections may occur in various foci, such as mucosa, catheters, and respiratory and gastrointestinal tracts [6], which may subsequently result in bacteremia during the period of severe neutropenia. Perianal or rectal abscesses are uncommon in immunocompetent subjects [2] but they may occasionally occur in leukemia or other neutropenic patients [2,7,8,9,10]. In patients with acute leukemia receiving chemotherapy, the incidence of perianal abscess is 5-9% [1,11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiology profiles differ among various studies [1,14]. Surgical interventions should be advised in most immunocompetent patients with a perianal abscess [2,3,4]. Surgical treatment for leukemia patients with a perianal abscess has been reported [12,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its development may be favored by anti-inflammatory medications and diabetes. The microbial flora is of fecal origin, often with mixed bacteria, mostly Escherichia coli or Klebsiella pneumoniae (the latter especially in diabetics) [4]. Antibiotic treatment alone without adequate drainage is ineffective.…”
Section: Treatment Of the Abscessmentioning
confidence: 99%